Model Collaborative Governance untuk Pengelolaan CSR pada UMKM di Kabupaten Muara Enim - Kurniawan Kurniawan; Waspodo Waspodo; Raniasa Putra (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2025)
This research aims to explore and develop a collaborative governance model in the management of Corporate Social Responsibility (CSR) oriented towards empowering Micro, Small, and Medium Enterprises (MSMEs) in Muara Enim Regency. Using a qualitative approach with case studies, this study analyzes the practice of collaboration between actors—local governments, companies, and MSME actors—and identifies supporting and inhibiting factors in the implementation of participatory and sustainable CSR. The findings show that the existing conditions of CSR management are still in the early stages with limited structures, regulations, and participation of MSMEs. Based on these findings, this study proposes the SIGER-MU (Responsive Governance Synergy for MSME Management) model as an integrative solution that emphasizes equal involvement between parties, participatory planning, inclusive institutions, and impact-based evaluation. This model is expected to strengthen the effectiveness of CSR programs and increase the independence of MSMEs as actors of local economic development.